Responding to a Forest Catastrophe: The Emergence of New Governance Arrangements in Southern California. (26th February 2014) - Petersen, Brian; Wellstead, Adam M.
Abstract : The San Bernardino National Forest in southern California experienced an unprecedented bark beetle outbreak in the early 2000s. The outbreak, coupled with a looming threat of catastrophic wildfire, droughts, changing forest management priorities, and a legacy of poor forest management practices coalesced to create a challenge that existing institutions and management agencies could not address. In response, an interagency collaborative effort, the Mountain Area Taskforce (MAST), was initiated. Based on key informant interviews, this paper details how this new governance organization emerged and how it effectively addressed a landscape scale forest challenge. Forest governance analyses often focus attention on macroscales, overlooking the microlevel arrangements that set MAST apart from other responses to bark beetle outbreaks. Interagency collaboration has taken on greater importance in efforts to address forest management at landscape scales and this case study provides important insights into the challenges and opportunities of these new governance arrangements.